Faktor Risiko Kejadian Dispepsia di Wilayah Kerja Puskesmas Amahai - Wiwi Rumaolat; Sunik Cahyawati (FORIKES, 2021)
Dyspepsia is the name for a syndrome in the form of pain or discomfort in the gut, nausea, bloating, vomiting, belching, feeling full quickly, and the stomach feeling full / full. This study aims to determine the factors associated with the incidence of dyspepia in the work area of the Amahai Public Health Center, Amahai District, Central Maluku Regency in 2019. The design of this type of research uses an observational research method with a case-control research design. The study ampel size was 68 cases and 68 controls. In being collected from medical record documents, then the Odd ratio is calculated. The results showed that there was a relationship between the incidence of dyspepsia with knowledge (OR = 4.696), diet (OR = 6.714); and there was no relationship between the incidence of dyspepsia and attitude (OR = 0.860). Key words: knowledge; attitude; dietary habit; the incidence of dyspepsia ABSTRAK Dispepsia merupakan sebutan untuk suatu sindroma berupa nyeri atau rasa tidak nyaman pada ulu hati, mual, kembung, muntah, sendawa, rasa cepat kenyang, dan perut merasa penuh/begah. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan kejadian dispepia di wilayah kerja Puskesmas Amahai Kecamatan Amahai Kabupaten Maluku Tengah pada tahun 2019. Desain jenis penelitian ini menggunakan metode penelitian observasional dengan rancangan penelitian case-control. Ukuran ampel penelitian adalah 68 kasus dan 68 kontrol. Dalam dikumpulkan dari dokumen rekam medik, selanjutnya dilakukan penghitungan Odd ratio. Hasil penelitian menunjukkan bahwa ada hubungan antara kejadian dispepsia dengan pengetahuan (OR = 4,696), pola makan (OR = 6,714); dan tidak ada hubungan antara kejadian dispepsia dengan sikap (OR = 0,860). Kata kunci: pengetahuan; sikap; pola makan; kejadian dispepsia